Morfoanatomia e teores de nutrientes em gemas de pereira - Silva, Ana Lúcia Pereira Nascimento da (2012)
The pear crop in southern Brazil emerges as a consistent alternative to the diversification of temperate fruit. However, temperature variations influence the physiological processes involved in internal input and output dormancy that may be connected to the anatomy, physiology and metabolism of the plant. Therefore, this study aimed to evaluate the characteristics and the possible involvement morphoanatomic levels of protein, carbohydrate, calcium and iron flower bud abortion in pear cultivar Nijisseik, in southern Brazil. It were determined the numbers of primordia, doubles inflorescences, length, diameter, volume, total carbohydrate content, total protein content, calcium and iron in gems. The number of primordia was higher in the second and the fourth harvest showing sharp reduction from fourth to fifth collection. The first to the second collection was significantly decreased length of gems, with a slight increase which was maintained in the other harvests. The diameter and volume decreased during the collections. The total carbohydrate had variations during the months of collection, a reduction during the month of august with a significant drop until september. A significant increase in protein concentration was determined from august to september, at this time there was an increase in temperature and reduction in hours of cold. The calcium content was reduced during the months from june to august and subsequent increase until september. Iron had a small reduction from june to july and after had increased as the months passed. According to the results, it can be concluded that the greater the number of origins, the greater the number of double inflorescence and the greater the intensity of necrosis. This fact can be considered as one of the first factors to trigger abortion, followed by lack of nutrients. Abortion may be involved with the reduction of total carbohydrate, and a shortage of calcium and also with increased iron in the period of dormancy of the buds. Perhaps the total proteins not have an effective involvement in bud abortion. The bud abortion is not caused by just one factor, but several factors may be interrelated, necessitating the continuation of studies covering the possible causes of this problem.